Numerical Simulation of Solar-Flue Gas Chimney for Energy Recovery - Khor, Yin Yin (Universiti Teknologi Petronas, 2009)
A solar-flue gas chimney is an energy recovery model utilizing solar energy and thermal energy from flue gas discharged from power plant to produce convective flow which drives wind turbine to generate electricity. This solar-flue gas chimney has three essential components, known as solar-flue gas collector, chimney and turbine.